A Pilot Clinical Study on the Efficacy of Sthoulyahara Choornam in the Management of Sthoulya w.s.r. to Obesity - Jaykrishan Barman,; Suvendu Rout,; Pradeep Kumar Moharana, (International Journal of Ayurveda and Pharma Research, 2023)
Obesity is a condition in which excess body fat has accumulated in different parts of the body mainly in the subcutaneous tissues. It hurts health and leads to reduced life expectancy as well as increased health problems. The World Health Organization has identified obesity as a global epidemic. The term “Sthoulya” is described in Ayurveda as “Overweight and Obesity”. This study was undertaken to identify the efficacy of Sthoulyahara Choornam (Anubhuta Yoga of SJSAC & H, which is in use for its in-house patients since 25 years). The ingredients of Sthoulyahara Choornam are mentioned in Charaka Samhita in the treatment of Medoroga. A total of 10 patients of either sex of age group 20-60 years were randomly selected from OPD & IPD of Sri Jayendra Saraswathi Ayurveda College & Hospital, Nazarethpettai, Chennai, 600123. They were treated with Sthoulyahara Choornam in doses of 2mg thrice a day after food with lukewarm water for 30 days (one month). Sthoulyahara Choornam was found to have a significant effect in reducing the symptoms of Medodushti and in the reduction of objective parameters like Bodyweight, B.M.I., skinfold thickness, and lipid profile.